Factors Associated With Victorian Adolescents' Harm Perceptions and Attitudes About e‐Cigarettes - Ian Koh; Maree Scully; Emily Baker; Melanie Wakefield; Victoria White; Sarah Durkin (Health Promotion Journal of Australia, 2026)
ABSTRACT Issue Addressed To explore Australian adolescents' perceptions of the risks and health harms associated with vaping and their attitudes towards e‐cigarettes and examine if these vary by demographic and other factors. Methods Data were from a 2022‐2023 cross‐sectional, school‐based survey of Victorian students aged 12–17 years ( n = 1701 [weighted]; n = 1696 [unweighted]). Separate multivariable logistic regression models tested associations between agreement with each perception/attitude and predictors (age group, gender, area‐based socio‐economic status, vaping susceptibility, e‐cigarette marketing exposure, peer vaping), controlling for education sector and school‐level clustering. Results Most students (≥ 86%) agreed that vaping is harmful and addictive and that e‐cigarettes contain harmful substances and nicotine, while agreement that breathing other people's e‐cigarette vapour can affect your health was somewhat lower (69%). Perceptions of vaping harms tended to be stronger among females (vs. males) and weaker among past‐month vapers (vs. non‐susceptible, never‐vapers). Overall, students held more negative than favourable attitudes towards e‐cigarettes. However, vaping susceptibility, being of younger age and having a close friend that vapes were independently associated with having more favourable attitudes towards e‐cigarettes (e.g., they look cool, make vaping look exciting). Further, past‐month exposure to e‐cigarette advertising was associated with students believing that e‐cigarettes look good, make vaping look appealing, encourage them to vape and encourage them to buy an e‐cigarette. Conclusions Findings provide support for recent government policies to limit e‐cigarette advertising and retail access, and the delivery of youth‐targeted educational campaigns about vaping. So What? Ongoing monitoring is important to assess sustained change over time in e‐cigarette knowledge and attitudes among Australian adolescents, with this study providing an important pre‐reform baseline against which such changes can be evaluated.